2018
DOI: 10.1021/acsami.8b00135
|View full text |Cite|
|
Sign up to set email alerts
|

PEGylated Self-Assembled Nano-Bacitracin A: Probing the Antibacterial Mechanism and Real-Time Tracing of Target Delivery in Vivo

Abstract: Although nano-self-assemblies of hydrophobic-modified bacitracin A with poly(d,l-lactic- co-glycolic acid) (PLGA) (nano-BA) have demonstrated promising antibacterial activities, the application of nano-BA was severely compromised by low water solubility. In this study, a series of PEGylated PLGA copolymers were selected to conjugate with the N-terminus of bacitracin A to construct PEGylated self-assembled nano-BAs and to further develop nano-self-assemblies of bacitracin A with strong antibacterial potency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…In our previous study, the PEGylated Nano-BA 12K based mainly on BA-PEG-PLGA 12K -PEG-BA demonstrated strong antibacterial activities against a broad spectrum of bacteria, including S. pneumonia , yet induced relatively lower toxicity both in vitro and in vivo (Hong et al., 2018 ). The objective of the present research was to evaluate the possibility of using PEGylated Nano-BA 12K to treat both Penicillin-sensitive and -resistant PM.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the PEGylated Nano-BA 12K based mainly on BA-PEG-PLGA 12K -PEG-BA demonstrated strong antibacterial activities against a broad spectrum of bacteria, including S. pneumonia , yet induced relatively lower toxicity both in vitro and in vivo (Hong et al., 2018 ). The objective of the present research was to evaluate the possibility of using PEGylated Nano-BA 12K to treat both Penicillin-sensitive and -resistant PM.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In our previous study, the PEGylated Nano-BA 12K based mainly on BA-PEG-PLGA 12K -PEG-BA showed strong antibacterial activities against both Gram-positive and Gram-negative bacteria including S. pneumonia, yet induced relatively lower toxicity both in vitro and in vivo. 21 The objective of the present research was to evaluate the possibility of using PEGylated Nano-BA 12K to treat penicillin-resistant S. pneumonia. The antibacterial potency of PEGylated Nano-BA 12K was first tested against 13 isolates of S. pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Bacitracin in solution, used as control, was effective only against Gram (+) bacteria with MICs between 2 and 4 µM, while MICs against Gram (−) were higher than 128 µM. It was shown as well that PEGylation did not affect antibacterial activity; on the contrary, PEGylated bacitracin-PLGA exhibited high accumulation in inflammatory tissue and prolonged blood circulation [132]. This system could be efficiently used to design novel antibiotic nano-assemblies in the treatment of invasive infections.…”
Section: Self-assembled Ampsmentioning
confidence: 99%